Impact of pulsed electric fields (PEF) treatment on the peeling ability of tomatoes and kiwi fruits - Giancaterino, Marianna; Jaeger, Henry (Frontiers in Food Science and Technology, 2023)
Peeling is a standard food processing operation that removes the outer layer of fruits and vegetables. It can improve the appearance and texture of many fruits and vegetables and is often necessary for further food preparation. Developing new and innovative peeling methods to minimise losses and enhance product quality is an area of active research in the food industry. The objective of this study was to evaluate how PEF affects the peeling ability of tomatoes and kiwi fruits, as well as the chemical and physical characteristics of the resulting peeled products. In detail, monopolar exponential decay pulses were applied, with an electric field strength of 1.0 kV/cm and a resulting total energy input in the range of 0.6 and 5.0 kJ/kg for tomatoes and 1.2 and 12.6 kJ/kg for kiwi fruits. Two methods were used to compare the effectiveness of PEF treatments with traditional peeling methods: hot-water blanching (98°C for 60 s) and lye peeling (98°C for 45 s, in 2% NaOH solution). The peeling efficiency was evaluated through manual and mechanical methods as well as measuring weight loss. The quality of the final peeled product was assessed by mechanical properties of the pericarp, colour (L*, a*, b* scale), ascorbic acid content, chlorophyll a and b, carotenoids, total polyphenols content and antioxidant activity. The PEF treatment applied to whole red tomatoes (1.0 kV/cm, 5.0 kJ/kg) and whole kiwi fruits (1.0 kV/cm, 12.6 kJ/kg) resulted in a significant decrease (p ≤ 0.05) of up to 43% and 83% in the force required for mechanical peeling, respectively. The PEF treatment showed comparable or superior peeling ability and significantly reduced product losses compared to hot-water blanching and lye peeling methods. However, the softening and the weight losses tend to increase by increasing the pulses for both investigated matrices. Moreover, by applying PEF instead of blanching or lye peeling, the chemical quality and the colour were better preserved (ΔE < 2). This study proved that PEF could be a promising non-thermal technology to better peel tomatoes and kiwi fruits without affecting their final quality. Consequently, applying PEF as a treatment to facilitate peeling has remarkable potential as an industrial application to reduce energy consumption and issues related to wastewater management typically occurring during the peeling with lye agents.